Cyberbully Detection Survey: Malay-English Glossary of Cyberbullying Incidents - Din M.M.; Rahim F.A.; Anwar R.M.; Bakar A.A.; Latif A.A. (Springer Science and Business Media Deutschland GmbH, 2024)
This article presents the results of a survey conducted to elicit keywords or phrases relating to cyberbullying incidents in both English and Malay languages commonly used in Malaysian society. The keywords or phrases can be utilized as a Malay and English cyberbullying glossary in the development of an auto-detection cyberbullying tool. A set of questionnaires were distributed among 329 respondents ages 1530years in Malaysia in the form of an online survey over one-and-a-half-month starting 1 November 2021. This study was conducted to test the items reliability using Cronbachs alpha values. There are three (3) Sections to this questionnaire